A methodology for formal analysis and verification of EAST-ADL models - Kang, Eun-Young; Enoiu, Eduard Paul; Marinescu, Raluca; Seceleanu, Cristina; Schobbens, Pierre-Yves; Pettersson, Paul (Reliability engineering & system safety, 2013)
The architectural design of embedded software has a direct impact on the final implementation, with respect to performance and other quality attributes. Therefore, guaranteeing that an architectural model meets the specified requirements is beneficial for detecting software flaws early in the development process. In this paper, we present a formal modeling and verification methodology for safety-critical automotive products that are originally described in the domain-specific architectural language East-adl. We propose a model-based approach that integrates the architectural models with component-aware model checking, and describe its tool support called ViTAL. The functional and timing behavior of each function block in the East-adl model, as well as the interactions between function blocks are formally captured and expressed as Timed Automata models, which have precise semantics and can be formally verified with ViTAL. Furthermore, we show how our approach, supported by ViTAL, can be used to formally prove that the East-adl system model fulfills the specified real-time requirements and behavioral constraints. We demonstrate that the approach improves the modeling and verification capability of East-adl and identifies dependencies, as well as potential conflicts between different automotive functions before implementation. The method is substantiated by verifying an automotive braking system model, with respect to particular functional and timing requirements.